Discovery of a highly selective VEGFR2 kinase inhibitor CHMFL-VEGFR2-002 as a novel anti-angiogenesis agent - Zongru Jiang; Li Wang; Xuesong Liu; Cheng Chen; Beilei Wang; Wenliang Wang; Chen Hu; Kailin Yu; Ziping Qi; Qingwang Liu; Aoli Wang; Jing Liu; et al. (Elsevier, 2020)
Angiogenesis is an essential process in tumor growth, invasion and metastasis. VEGF receptor 2 (VEGFR2) inhibitors targeting tumor angiogenic pathway have been widely used in the clinical cancer treatment. However, most of currently used VEGFR2 kinase inhibitors are multi-target inhibitors which might result in target-associated side effects and therefore limited clinical toleration. Highly selective VEGFR inhibitors are still highly demanded from both basic research and clinical application point of view. Here we report the discovery and characterization of a novel VEGFR2 inhibitor (CHMFL-VEGFR2-002), which exhibited high selectivity among structurally closed kinases including PDGFRs, FGFRs, CSF1R, etc. CHMFL-VEGFR2-002 displayed potent inhibitory activity against VEGFR2 kinase in the biochemical assay (IC50 = 66 nmol/L) and VEGFR2 autophosphorylation in cells (EC50s ∼100 nmol/L) as well as potent anti-proliferation effect against VEGFR2 transformed BaF3 cells (GI50 = 150 nmol/L). In addition, CHMFL-VEGFR2-002 also displayed good anti-angiogenesis efficacy in vitro and exhibited good in vivo PK (pharmacokinetics) profile with bioavailability over 49% and anti-angiogenesis efficacy in both zebrafish and mouse models without apparent toxicity. These results suggest that CHMFL-VEGFR2-002 might be a useful research tool for dissecting new functions of VEGFR2 kinase as well as a potential anti-angiogenetic agent for the cancer therapy. KEY WORDS: Cancer, VEGFR2 kinase, Kinase inhibitor, Angiogenesis, Inhibitor selectivity